2023
DOI: 10.1113/jp283362
|View full text |Cite
|
Sign up to set email alerts
|

Lifelong exposure to high‐altitude hypoxia in humans is associated with improved redox homeostasis and structural–functional adaptations of the neurovascular unit

Abstract: Wales and member of the Neurovascular Research Laboratory led by Professor Damian Bailey where he completed his PhD. Damian M. Bailey is a Royal Society Wolfson Research Fellow and Professor of Physiology and Biochemistry at the University of South Wales. He is Editor-in-Chief of Experimental Physiology and Chair of the Life Sciences Working Group to the European Space Agency. The Neurovascular Research Laboratory takes an integrated translational approach to investigate how free radicals and associated reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 117 publications
0
3
0
Order By: Relevance
“…Recently, life-long chronic continuous hypoxia (F I O 2 of 11%) has been demonstrated to protect the brain in animal models of neurological diseases such as Leigh syndrome [96,97] or Friedreich ataxia [98], presumably by correcting the diseaseinduced increased levels of oxygen in the brain, which may promote oxidative stress. Furthermore, living at higher altitudes is associated with improved function and structure of the neurovascular unit in populations such as Andean highlanders [99] and a reduced risk of stroke in moderate-altitude residents in the Alps [100]. Chronic, mild, and continuous hypoxia may therefore protect the brain by optimizing cardiovascular parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, life-long chronic continuous hypoxia (F I O 2 of 11%) has been demonstrated to protect the brain in animal models of neurological diseases such as Leigh syndrome [96,97] or Friedreich ataxia [98], presumably by correcting the diseaseinduced increased levels of oxygen in the brain, which may promote oxidative stress. Furthermore, living at higher altitudes is associated with improved function and structure of the neurovascular unit in populations such as Andean highlanders [99] and a reduced risk of stroke in moderate-altitude residents in the Alps [100]. Chronic, mild, and continuous hypoxia may therefore protect the brain by optimizing cardiovascular parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on neurological impairment in people living at high altitudes are lacking. However, a recent study by Stacey and colleagues showed that the cognitive function of native highlanders from Cerro de Pasco (4300 m) was not altered compared with that of a lowlander group, whereas cognitive impairment was observed in lowlanders after two weeks of highaltitude exposure (4300 m) [126]. These findings are consistent with a previous study in rats exposed to hypobaric hypoxia (6100 m) for 3, 7, 14, and 21 days, which showed that memory impairment was alleviated and antioxidant levels were decreased on day 21 compared to day 7 [127].…”
Section: Chronic Hypobaric Hypoxia (Chh)mentioning
confidence: 94%
“…As global warming contributes to hotter summers (3 July 2023 recorded the hottest global temperatures yet; Dickie, 2023), OXINOS may predispose to cardio-cerebro-metabolic dysfunction in vulnerable populations and tip the scales toward maladaptation. This 'tipping point' from the hormetic adaptive towards the OXINOS-mediated maladaptive phenotype has been observed in lowlanders travelling to high-altitude suffering from acute mountain sickness (Bailey et al, 2009) and high-altitude pulmonary oedema (Bailey et al, 2010), to native highlanders suffering from the debilitating syndrome of chronic mountain sickness (Bailey et al, 2019;Stacey et al, 2023). Heat stress and chronically elevated OXINOS 'consumes' the physiological reserve, further enhancing cerebral vulnerability (Low et al, 2009;Wilson et al, 2006).…”
mentioning
confidence: 92%